2011
DOI: 10.1149/1.3529948
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bonding of Silicon to Platinum

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Direct bonding 1,2 of semiconductor wafers have gained much research and commercial interests. These efforts have led to a number of new opportunities for devices such as three-dimensional (3D) integrated circuits, 3,4 3D integration for vertical interconnection, 5 micro electro mechanical systems (MEMS) technology, 6 silicon on insulator (SOI), 7 multi-junctions photovoltaic devices, 8 and other types of devices. The attractiveness of direct bonding is that can be initiated on almost any material when two properly prepared surfaces are brought into contact in room ambient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct bonding 1,2 of semiconductor wafers have gained much research and commercial interests. These efforts have led to a number of new opportunities for devices such as three-dimensional (3D) integrated circuits, 3,4 3D integration for vertical interconnection, 5 micro electro mechanical systems (MEMS) technology, 6 silicon on insulator (SOI), 7 multi-junctions photovoltaic devices, 8 and other types of devices. The attractiveness of direct bonding is that can be initiated on almost any material when two properly prepared surfaces are brought into contact in room ambient.…”
mentioning
confidence: 99%
“…Generally, good direct bonding requires the surface of the two pairing wafers to be clean and free from particles and any form of contaminations with root-mean-square (RMS) roughness <1 nm. 8 For example, one report has indicated that high quality bonding 3 require mirror-polished wafer with the RMS roughness typically ∼0.5nm. In most applications, enhancement of the hydrophilicity of the wafer surface can be achieved by introducing the O 2 activation 9 as it increases the surface energy of the wafer surface prior to the bonding.…”
mentioning
confidence: 99%